How we got the New Testament : text, transmission, translation - Porter, Stanley E., 1956- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2013)
"This volume offers a historical understanding of the writing, transmission, and translation of the New Testament and provides cutting-edge insights into how we got the New Testament in its ancient Greek and modern English forms. The author, a recognized expert in New Testament Greek, offers a student-level summary of a vast amount of historical and textual information. Responding to those who question the New Testament's reliability, Stanley Porter rigorously defends the traditional reason for textual criticism--to establish the original text or get as close to it as possible--and shows that this is still a reasonable goal. He reveals fascinating details about the earliest New Testament manuscripts and argues that the textual evidence supports an early date for the New Testament's formation. He also distinguishes between continuous text manuscripts and those that offer only excerpts, thereby providing a helpful nuance for textual criticism. Porter concludes by exploring the vital role translation plays in biblical understanding and evaluating various translation theories" -- Publisher description.
The text of the New Testament -- The transmission of the New Testament -- The translation of the New Testament.
Includes bibliographical references and index.
Keywords: Bible -- History